PERMINTAAN KONSUMEN REKREASI ALAM OBJEK WISATA PANTAI PULAU DATOK KABUPATEN KAYONG UTARA - Wahyudin, Tsalas; Muin, Sudirman; Widiastuti, Tri (JURNAL HUTAN LESTARI, 2017)
Tourism Object Coast Datok Island is one of the leading tourist attraction found in Kayong Utara District. The purpose of this study to determine the level of consumer demand, the ratio of travel costs between Datok Island Beach and Air Pauh. The data were collected for Â± 4 weeks in the field. The method used is interview technique with quesioner tool. Sampling was done by accidental sampling and the number of samples were 60 respondents. The result of the research shows that the level of consumer demand is low (66.67%) only visit 1-2 times / month this is because the visitors are dominated by local residents with distance of living not far from Datok Island Beach. There is a significant difference between travel costs Datok Island Tourist Attraction with Air Pauh Tourism Object.Keywords: nature recreation, Pulau Datok Beach, recreation requests, tourists